The Ameliorating effect of uncooked beans diet in CD-1 mice - W, Aduema; JU, Agbai (Innovare Journal of Medical Sciences, 2018)
Beans contain serotonin and its precursor, 5-Hydroxytryptophan which have neurobehavioral actions on memory, anxiety, mood and pain. This study was therefore, designed to investigate the ameliorating effect of uncooked beans on pain sensation using three groups of Swiss white mice (control and test) weighing 18g-35g (n=10 each).The control group received normal rodent chow, while the test group received 50g of uncooked beans in 50g of rodent chow per day and serotonin precursor (5HTP) (0.2mg/50g w/w) diet. Water was given adlibitum while daily food and water intake, as well as body weight changes, were monitored during the 30-day study. The formalin tests were used to assess pain sensation. The results showed that in the formalin test, the frequency and duration of paw attention in both phases of the test was significantly lower (P< 0.05) compared to the control group. The duration and frequency of paw licks (P<0.05) was also significantly lower in the uncooked beans diet and serotonin precursor group compared to the control. Therefore, consumption of uncooked beans diet may decrease pain sensation.